Manipulation of the Duration of the Initial Self-Control Task Within the Sequential-Task Paradigm: Effect on Exercise Performance - Boat, Ruth; Hunte, Raymon; Welsh, Emily; Dunn, Anna; Treadwell, Ellen; Cooper, Simon B. (Frontiers in Neuroscience, 2020)
The completion of a task, requiring self-control, has been associated with impaired performance on subsequent physical tasks also requiring self-control; an effect suggested to be mediated by changes in perceptions of pain and motivation. However, the effects of spending longer on the initial self-control task are unknown. This study, therefore, explored the potential for the duration of the initial self-control task to influence subsequent physical performance, perceptions of pain, and perceived motivation; particularly during the early stages of the physical task. In a within-subject design, 29 participants (11 male, 18 female) completed a wall-sit task until volitional exhaustion, on four separate occasions. Prior to each wall-sit, participants completed either a non-self-control task (congruent Stroop task) for four minutes, or a self-control task (incongruent Stroop task) for four (short duration), eight (medium duration), or sixteen (long duration) minutes. Participant’s perceptions of pain and motivation were recorded every 30 seconds during the wall-sit. Wall-sit performance time was analysed using one-way ANOVA and perceptions of pain and motivation analysed using multi-level modelling. Wall-sit performance time was significantly longer on the non-self-control exertion trial compared to all other trials (all p<0.01), as well as longer on both the short duration and medium duration self-control exertion trials compared to the long duration self-control exertion trial (both p<0.001). Perceptions of initial (at 30 seconds) pain and motivation were different between the trials (main effect of trial: pain, p=0.001; motivation, p<0.001); whereby longer durations of self-control exertion increased perceptions of pain and decreased perceived motivation. The decrease in motivation during the wall-sit task was greater on the long duration self-control exertion trial compared to all other trials (trial*time interactions, all p<0.05). The present study provides novel evidence that spending longer on the initial self-control task led to greater detrimental effects on subsequent wall-sit performance time. Furthermore, longer duration self-control exertion tasks led to increased perceptions of pain and decreased perceptions of motivation within the first 30 seconds of the wall-sit task, as well as a greater decrease in motivation across the wall-sit task. These attentional and motivational shifts may explain performance decrements following the exertion of self-control.